Eksplorasi Pengalaman Emosional Siswa Dalam Kegiatan Mozaik Biji-Bijian di Sekolah Dasar - Nugroho, Anang Amiruddin; Alfarisi, Muhammad Adha; Pratiwi, Kayla Audi Anggun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to explore students emotional experiences during the implementation of a seed mosaic activity in elementary school. The research is grounded in the importance of understanding the emotional dimension in the learning process, particularly in art activities that require perseverance, concentration, and collaboration. This study employed a qualitative approach with an exploratory design. Data were collected through observations of students activities, in-depth interviews with both students and teachers, and documentation of the mosaic artworks. The data were analyzed thematically to identify patterns of emotional experiences encountered by students throughout the activity. The findings indicate that the seed mosaic activity elicited a range of emotional experiences, including enthusiasm, curiosity, frustration, focus, perseverance, and pride in the completed work. These emotions developed dynamically throughout the mosaic-making process. The activity was shown to help students practice emotional regulation, enhance student engagement, and strengthen social interaction among students within a supportive classroom environment. These findings suggest that the seed mosaic activity not only contributes to the development of creativity but also plays a significant role in supporting students emotional and social development in elementary school.